Synthesis, characterization and thermal properties of a novel star polymer consisting of poly(?-caprolactone) arms emanating from an octa-functional porphyrazine core - Celik, Asuman; Kemikli, Nurufe; Ozturk, Ramazan; Muftuoglu, Ali Ekrem; Yilmaz, Faruk (Elsevier, 2009)
Octaarmed star-shaped poly(epsilon-caprolactone) (OSPCL) was successfully synthesized via the ring-opening polymerization (ROP) of epsilon-caprolactone (epsilon-CL) with a magnesium porphyrazine as the multisite initiator and tin(II) 2-ethylhexanoate (Sn(Oct(2))) as the catalyst in bulk at 115 degrees C. The star polymer has a central Mg-porphyrazine surrounded by epsilon-CL arms. OSPCL was characterized by H-1 NMR, FTIR, GPC and UV-vis, and fluorescent spectroscopy. The effect of the molar ratio of the monomer to the initiator on molecular weight of the polymer was also investigated. The molecular weight of the polymer linearly increased with increasing molar ratio of the monomer to the initiator. The crystallization behavior of OSPCL was studied using differential scanning calorimetry (DSC) and polarizing optical microscopy (POM). OSPCL displayed an interrupted crystal morphology owing to its highly branched architecture, and consequently, the degree of crystallinity was lower in comparison with the linear analogue. Thermogravimetric analysis (TGA) clearly indicated that incorporation of porphyrazine core enhanced the thermal stability of the resulting polymers. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Star-shaped poly(epsilon-caprolactone); Ring-opening polymerization; Porphyrazine initiator; Crystallization